implementasi Implementasi Model Pembelajaran Problem Based Learning (Pbl) Untuk Meningkatkan Keterampilan Passing Bawah Bola Voli - Afifatul, Mochammad Khoirul; Tjahyo Kuntjoro, Bambang Ferianto; Ismayadewi, Ciciek (STAMINA, 2024)
The problem in this assessment is that there are still many students who have low basic downward passing skills. The purpose of the study was to improve the passing skills of volleyball students in class VIII B at SMP Negeri 11 Surabaya with the Problem Based Learning (PBL) learning model. This assessment uses a class action assessment (PTK). The subjects in the assessment are students of class VIII B at SMP Negeri 11 Surabaya which has a total of 31 students. This study uses quantitative descriptive data analysis techniques. From the data of Pre-Cycle, cycle I and cycle II, there is a success or improvement in volleyball passing skills in students. This is evidenced by an increase in the average score acquisition and classical completeness of students. In the pre-cycle, it was found that the average score was around 69.74 and classical completeness was 25.80%. In the first cycle, it was found that the average score was around 74.45 and calcital completeness was 48.39%. while in the second cycle it was found that the average score was around 80.70 and the classical completeness was 83.87%. This shows that there is an improvement in volleyball passing skills with the implementation of the Problem Based Learning learning model